Modification of Peck Formula to Predict Ground Surface Settlement of Twin Tunnels in Low Permeability Soil - Xiaowu Tang; Jiaxin Liang; Wei Liu; Yuhang Ye; Penglu Gan; Wenfang Zhao; Yue Yu (Advances in Civil Engineering)
Accurate prediction of surface settlement induced by tunnel excavation is significant for preventing damage to existing structures under complex geological conditions. The Peck formula is currently considered as an efficient solution for surface settlement prediction. This paper proposes a modified Peck formula considering geological conditions to improve the accuracy of surface settlement prediction of twin tunnels. The asynchronization of the sinking rate and stability of the vault settlement and surface settlement within the river-affected area may attribute to the groundwater drawdown caused by cofferdam construction on the river. A modified Peck formula is put forward with soil permeability and width-controlling parameters involved. There is a small settlement at the center of the twin tunnels, making the settlement trough upward buckling, which is like a “W” shape. This situation can be accurately predicted by the modified formula with a significantly increased adjusted R-square. The modified formula can accurately predict the surface settlement of tunnels excavated in low permeability soil layers with a permeability coefficient between 10−4 cm/s and 10−7 cm/s, especially in the groundwater drawdown environment. The reliability of the modified Peck formula is verified by other cases in Nanjing and Singapore.